234 Sleep quality during the coronavirus pandemic in a Brazilian family-based cohort. (3rd May 2021) - Taporoski, Tamara; Beijamini, Felipe; Ruiz, Francieli; Ahmed, Sabrina; von Schantz, Malcolm; Pereira, Alexandre; Knutson, Kristen
Abstract: Introduction: Early in the COVID-19 pandemic, Brazil adopted measures to minimize the spread of the virus, including quarantine orders where people only left home for essential business. This practice could negatively impact sleep by reducing exposure to daylight and physical activity. We examined subjective sleep quality in Baependi, a small rural town in Brazil during the COVID-19 quarantine order. Methods: This sample is from the Baependi Heart Study, a family-based cohort of adults. Participants (n=800, 71% women, mean age 51.6±15.6 years) completed the Pittsburgh Sleep Quality Index (PSQI) early in the COVID pandemic (April-May, 2020). They were also asked about their compliance to the quarantine order (yes/no). We compared sleep between quarantined (QT) and not-quarantined individuals (NQT). Longitudinal data was obtained from a subsample of 417 individuals who also completed a pre-COVID PSQI between January, 2010 and September, 2014. Results: Individuals compliant with the quarantine had worse sleep quality than non-quarantined individuals [QT PSQI= 6.1 (±3.9), NQT PSQI= 5.0 (±3.5), p<0.01]. Stratified analysis showed that differences in PSQI scores between QT and NQT was greater for women [QT = 6.4 (±4), NQT = 5.2 (±3.7), p<0.01] and older people [QT = 6.6 (±0.1), NQT = 5.5 (±3.3), p=0.02]. Associations were attenuated after adjusting for age and gender. PSQI components demonstrated a higher sleep latency for the QT group in the full sample (p=0.02), women (p<0.01) and young (<50 years, p=0.03). Sleep duration was shorter in the QT young subsample (p=0.03). QT women also reported lower sleep efficiency (p=0.01) and greater use of sleep medication than NQT women (p<0.01). In the longitudinal subsample, PSQI scores were significantly higher during COVID than pre-pandemic [COVID= 5.7 (±3.8), pre-COVID= 5 (±3.3), p<0.01]. The significant change in PSQI was only observed in the QT participants [COVID= 5.9 (±3.7), pre-COVID= 5.2 (±3.4), p<0.01] and not NQT [COVID= 5 (±3.7), pre-COVID= 4.5 (±3), p=0.12. Conclusion: Individuals who quarantined during COVID-19 had worse sleep quality than individuals who did not quarantine. Longitudinal comparison demonstrated that participants who quarantined had worse sleep quality during COVID compared to before to the pandemic. Support (if any): NIH 1R01HL141881